Assure as a Learning Model: Empirical Study on Intensive Course Lecturer in English Department - Siti Maria Ulfa (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2017)
This research investigates the implementation of ASSURE learning model in Intensive Course and also investigates the responses of the students. ASSURE learning model. It consists of several steps like analyzing the learners, stating the standards and objectives of the study, choosing and utilizing media, requiring learners' participation and the last is revising and evaluating. The whole data is analyzed by ASSURE learning model is applied. The result of this research was found that the Assure learning model is done effectively through the use of sequence of teaching and learning process. The implementation of this learning model has contributed a very good athmosphere in Intensice Course classroom. By analyzing students firstly, and then choosing the right media and finally doing some evaluation, the teaching and learning process was quite interesting and students felt different or various ways in learning new course. As a conclusion, the steps which are stated in the learning model is done gradually and appropiately with what the objectives and the sequence of process. And it is also hoped that through this research, the Intensive Course in first semester in English Department actually has the orientation of creating effective teaching and learning process